2015
DOI: 10.1021/ac5038208
|View full text |Cite
|
Sign up to set email alerts
|

Bioluminescent Liquid Light Guide Pad Biosensor for Indoor Air Toxicity Monitoring

Abstract: Indoor air pollution became a recent concern found to be oftentimes worse than outdoor air quality. We developed a tool that is cheap and simple and enables continuous monitoring of air toxicity. It is a biosensor with both a nondisposable (monitor) and disposable (calcium alginate pads with immobilized bacteria) elements. Various parameters to enhance its signal have been tested (including the effect of the pad's orientation, it's exposure to either temperature or time with the air toxicant analyte, and vario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 60 publications
(85 reference statements)
0
25
0
Order By: Relevance
“…In the last years, chemical sensors have been the subject of intensive research owing to public health issues regarding increasing environmental pollution . Indeed, finding suitable sensors to detect harmful chemical substances (air pollutants) is in high demand . The detection of VOCs (volatile organic compounds) by simple means with a low‐cost technology is therefore a main research area .…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…In the last years, chemical sensors have been the subject of intensive research owing to public health issues regarding increasing environmental pollution . Indeed, finding suitable sensors to detect harmful chemical substances (air pollutants) is in high demand . The detection of VOCs (volatile organic compounds) by simple means with a low‐cost technology is therefore a main research area .…”
Section: Figurementioning
confidence: 99%
“…[7] Indeed,f inding suitable sensorst od etect harmful chemical substances (air pollutants) is in high demand. [8] The detection of VOCs (volatile organic compounds) by simple means with al ow-cost technology is therefore am ain research area. [9] In this context,a mong the class of luminescent stimuli-responsive materials, those exhibiting luminescence vapochromism or solvatochromism properties, whicha re characterizedb yc hanges in lumines-cence properties upon exposure to solvents in vapor or liquid state,a re particularly relevant.…”
mentioning
confidence: 99%
“…A great variety of applications, ranging from toxic chemical detection to disease diagnostics has been investigated [5][6][7] and these studies have found practical uses on an individual consumer level, such as fire or natural gas alarms. However, there are challenges in the commercialization of gas sensors for applications where identification of multiple chemicals is required, such as food and water safety and environmental monitoring [8,9]. For instance, for indoor air quality monitoring, the target molecules are an enormous range of volatile organic compounds (VOCs) that evaporate from products such as paint, varnishes, cleaning supplies, pesticides, and furnishings [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…However, there are challenges in the commercialization of gas sensors for applications where identification of multiple chemicals is required, such as food and water safety and environmental monitoring [8,9]. For instance, for indoor air quality monitoring, the target molecules are an enormous range of volatile organic compounds (VOCs) that evaporate from products such as paint, varnishes, cleaning supplies, pesticides, and furnishings [9,10]. An analytical tool that can be used for such purposes should be able to accurately recognize a wide range of VOCs while addressing the challenges of complexity, size, and cost of conventional systems.…”
Section: Introductionmentioning
confidence: 99%
“…A similar prototype was previously published to monitor air toxicity [21]. The proposed water toxicity biosensor is comprised of two parts, non-disposable (photodetector) and disposable (part-composed of new calcium alginate pads with immobilized bioluminescent bacteria).…”
Section: Introductionmentioning
confidence: 99%